Approved budget for 1992: Oyo State of Nigeria - Oyo State (Nigeria) ([Ibadan] : [Oyo State], 1992)
This book contains an estimated budgetary allocation for Oyo state ministries and agencies for the year 1992. It includes overheads, security volts and other financial burden of the state government.
osa 23/04/19
Loans
Keywords: Budget; Expenditures, Public; Oyo State (Nigeria); Nigeria